E-business model innovation and capability building - Stéphane Gagnon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
A firm's business model describes the way in which it creates, delivers, and appropriates value. In the debate about the ongoing demise of several e-commerce ventures, only a few analysts have looked at the relative sanity of innovative e-business Models, relying mostly on static environmental variables and the inherent economic logic of each industry. Our study sheds new light on this debate by concentrating on a set of more complex factors, namely the relative difficulty to build new capabilities, whether by creating or acquiring them. We interviewed 60 e-commerce ventures between 2 and 3 years old, both independent and corporate ones, in order to measure their performance, the innovativeness of their e-business model, their obstacles to capability building, and their exploitable resource base. By performing cluster, discriminant, and regression analyses, we demonstrate that a number of typical obstacles to capability building can significantly affect the relative success or failure of innovative e-business models, but that a richer resource base may alleviate this relationship. We end with a discussion of the implications for the e-business model literature, and point out to some new directions to explain how various e-commerce firms, whether `pure-play' or `click-and-mortar', can successfully innovate despite rampant capability building difficulties.
Keywords: L29; M13; O32; 330; e-commerce; business models; capability building